Evaluation of thrombocytopenia in systemic lupus erythematosus patients in a tertiary care hospital: clinical implications and prognostic significance - Faruque, Farhana; Ismail Hossain, M.; Sarkar, Nayan Ranjan; Sufi Shafi-Ul-Bashar, S. M. (International Journal of Research in Medical Sciences, 2025)
Background: Thrombocytopenia is a common hematological complication in systemic lupus erythematosus (SLE), associated with increased disease severity and adverse outcomes. This study aimed to evaluate the clinical implications and prognostic significance of thrombocytopenia in SLE patients at a tertiary care hospital in Bangladesh. Methods: A cross-sectional study was conducted at the Sir Salimullah Medical College Mitford Hospital with 42 SLE patients. Data were collected on demographic characteristics, medical history, risk factors, clinical assessments, laboratory findings, and treatment outcomes. Statistical analyses were performed to identify associations between thrombocytopenia, disease severity, and outcomes. Results: The study population was predominantly female (73.81%) and aged 25-34 years (52.38%). Thrombocytopenia was present with a mean platelet count of 54,523±648.97/μl, and symptoms included easy bruising (35.71%) and petechiae (45.24%). Severe disease activity was observed in 80.95% of patients, with frequent hospitalizations and poor prognostic outcomes significantly associated with thrombocytopenia (p<0.05). Shorter disease duration correlated with more severe symptoms (r=0.52, p=0.018), and fewer disease flares were linked to better prognoses (r=0.49, p=0.015). Standard therapies yielded limited improvement, with 30.95% showing improvement, 33.33% experiencing no change, and 35.71% worsening. Conclusions: Thrombocytopenia is a significant marker of disease burden and poor outcomes in SLE patients. Comprehensive monitoring and personalized management strategies are essential to address its clinical and prognostic implications, particularly in resource-constrained settings.